Impact of Nutritional Educational Program on the Nutritional Habits and Status among Older Adults at Qena City, Egypt - Chih, Jun; Abdelnasser, Nadia Omar Emam; Ibrahim, Hoda Diab Fahmy; Hassan, Asmaa Kamal; Youssef, Mohamed Kamal Alsayed (2018)
Background: The age-related changes of the gastrointestinal tract, availability of the food and the functional ability affect the nutritional intake among elderly people. Most of the diseases originate from malnutrition especially among the vulnerable group as older adults. Therefore, the aim of this study is to improve older adults' nutritional habits. The study followed a quesi experimental research design and was carried out in the Elderly Club at Qena City. Sample; One hundred and six older adults who fulfilled the inclusion criteria participated in this study and assigned randomly into fifty-three intervention group and fifty-three control group. Two tools were used to collect the data; Tool I Structured Interview Form and tool II Mini-Nutritional Assessment Scale. The results of this study revealed that there are no statistically significant differences of frequency of usual food consumed per week between pre-test and Posttest among the intervention or control group (P > 0.05). There are significance differences between pre-test and Posttest of food preparation method and the substances used in cooking among only the intervention group. It was concluded from the current study that the intervention improved the nutritional habits. Based on the study results, it will be useful implement the nutritional educational program at all older organizations which provide services to older adults such as elderly homes, elderly clubs, and hospitals in Egypt.